Exploring the Multidimensional Links Between Trait Mindfulness and Trait Empathy - Himichi, Toshiyuki; Osanai, Hidekazu; Goto, Takayuki; Fujita, Hiroyo; Kawamura, Yuta; Smith, Adam; Nomura, Michio (Frontiers in Psychiatry, 2021)
Empathy and mindfulness are currently major topics of scientific interest. Although it is well known that mindfulness—typically as an outcome related to meditation—generates empathy at the state level, only a small number of studies have documented the trait (i.e., personality) level association between mindfulness and empathy. Furthermore, the underlying mechanisms (subcomponents and mediator variables) that support this association remain unclear. Thus, here, with a focus on the trait level, we investigated relationships among multiple subcomponents of trait mindfulness and trait empathy (Study 1). Next, we reexamined the aforementioned relationships in an independent sample, with the further aim of investigating relevant mediation factors (Study 2). We found that two attention-related components of trait mindfulness—observing and acting with awareness—reliably and positively related to both affective and cognitive dimensions of trait empathy (i.e., empathic concern and perspective taking). Furthermore, we found that effortful control, reappraisal, and trait alexithymia mediated relationships between the aforementioned attention-related components of trait mindfulness and empathic concern. Taken together, our results suggest that the links between mindfulness and empathy are multidimensional and complex. These findings may ultimately contribute to an understanding of the mechanisms underlying the positive effects of meditation on empathy.